A formative evaluation of the IPads for Education programme: A practical example illustrating the importance of programme implementation - Mogale, Nqobile Shelly (Institute for Monitoring and Evaluation, 2017)
Background: South Africa as a developing country is faced with the problem of insufficient resources that support learning in schools. This problem is mostly in schools from low income communities, whereby it contributes to the low academic performance observed in these schools. The iPads for Education Programme was implemented as a pilot study in Sentinel Primary School, Hout Bay, as a solution to low academic performance. The programme aimed to improve mathematics performance of grade five learners through the use of iPads as a teaching and learning device during school lessons. Objective: This dissertation reports a formative evaluation that was conducted on the iPads for Education Programme. Methods: The evaluation assessed the implementation of the programme and short-term outcomes for the learners using both qualitative and qualitative approaches. Results: The evaluation found the implementation of the programme to be weak and as such subsequent recommendations for improvement were made. Overall the research provides practical evidence of the importance of stakeholder engagement and buy-in for programme implementation.